Myositis associated with a newly described microsporidian, Trachipleistophora hominis, in a patient with AIDS. - Field, A S (1996)
Microsporidia are zoonotic protozoa which were rare human pathogens prior to 1985, when Enterocytozoon bieneusi was described in human immunodeficiency virus-infected patients with chronic diarrhea. Another species, Encephalitozoon (Septata) intestinalis, is associated with diarrhea and chronic sinusitis, and approximately 25 cases have been reported in the literature. However, other microsporidial infections in human immunodeficiency virus-infected patients remain extremely rare. We report the first case of a Pleistophora sp.-like microsporidian infection presenting as a progressive severe myosotis associated with fever and weight loss. The organism was demonstrated by light microscopy and electron microscopy in corneal scrapings, skeletal muscle, and nasal discharge. Electron microscopy showed an electron-dense surface coat with "sunflare"-like projections surrounding all stages of development of meronts (two to four nuclei, dividing by binary fission), sporonts, and sporoblasts. Division of sporonts, in which sporonts separate from the thick outer coat, creating a sporophorous vesicle, is by binary fission, differentiating this organism from Pleistophora sp. The spore measures 4.0 by 2.5 microns and has a rugose exospore. A new genus and species, Trachipleistophora hominis, has been established for this parasite. The patient was treated with albendazole, sulfadiazine, and pyrimethamine, and the clinical symptoms resolved.